SENSITIVITY AND SPECIFICITY OF ABDOMINAL FLUID VARIABLES AS A MARKER OF INTESTINAL ISCHEMIA IN DONKEYS (EQUUS ASINUS) - H. M. M. Ibrahim a; S. M. Shoieb b; M. R. El-Ashker a; K. S. Abouelnasr c (Journal of Animal and Plant Sciences, 2020)
The current study aimed to assess the cellular profile and certain biochemical parameters of the peritoneal fluid, highlighting their diagnostic sensitivity and specificity as biomarkers for early diagnosis of intestinal ischemia in donkeys. For this purpose, peritoneal fluid samples were collected from 30 donkeys (Equus asinus) with intestinal obstruction and 10 randomly selected clinically healthy donkeys (Equus asinus) (control group) for cytological examination and biochemical analysis of the activity of alkaline phosphatase and lipase, and level of lactate, nitric oxide, and cardiac troponin I. In comparison with control group, the count of total nucleated cells, neutrophils, lymphocytes, and monocytes increased significantly (P < 0.05). The cellular profile provoked 100% diagnostic sensitivity and specificity. Furthermore, the activity of alkaline phosphatase and lipase as well as the level of lactate, nitric oxide and cardiac troponin I in peritoneal fluid were greatly (P < 0.05) increased in comparison with control group. Peritoneal fluid biochemical parameters elicited variable diagnostic sensitivity; alkaline phosphatase activity (90 %), lactate level (90 %), lipase activity (80 %), nitric oxide level (80 %), and cardiac troponin I level (90 %), with specificity (100 %) for each. Multivariate logistic regression analysis of peritoneal fluid variables demonstrated that increased total nucleated cells count, increased activity of both alkaline phosphatase and lipase, and increased lactate level are important factors for predicting intestinal obstruction and ischemia in the studied donkeys. The present study demonstrated that the changes in the cellular profile of the peritoneal fluid as well as biochemical analysis of the activity of both alkaline phosphatase and lipase, and level of lactate, nitric oxide, and cardiac troponin I in the peritoneal fluid are sensitive and specific predictors to assist in the early diagnosis of intestinal obstruction in donkeys (Equus asinus) with obstructive colic. The recorded alterations in the peritoneal fluid variables in donkeys (Equus asinus) may be used as a model for intestinal obstruction and ischemia in horses as well as other animal species.
Keywords: Obstructive colic; Intestinal ischemia; Peritoneal fluid; Donkeys (Equus asinus)